Pengembangan Bahan Reflective ThinkingAjar dan Instrumen untuk Meningkatkan Berpikir Reflektif Matematis dan Kemandirian Belajar Berbasis Pendekatan Metakognitif - Hepsi, Hepsi (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2012)
This study mathematical background of reflective thinking skills are very important role in mathematical problem-solving activities. Based on the results of a preliminary study, 60% contained one high school students Tangerang district in Banten still weak in several indicators reflective mathematical thinking skills. In addition to reflective thinking that will be developed there to learn independence. Reflective mathematical thinking and independence associated with learning one's metacognitive abilities. Metacognitive ability is an ability that aware of his thinking, the ability to see herself so that what is done can be controlled optimally. The purpose of this study is to produce teaching materials and instruments and columns based learning approach to enhance metacognitive reflective mathematical thinking and learning independence. This research method using the method development. Its activities include preliminary studies (literature search, observation, interviews with teachers), product development (teaching materials and instruments and columns, test experts (mathematicians and mathematics education), Test 3 is limited to students in high school in Tangerang district belonging to high school, moderate and low. This study concluded that the teaching materials, instruments ability to think mathematically and learn self-reliance scale feasible for use. Instruments reflective mathematical thinking has 8 indicators with 11 questions and independence Scale consists of nine indicators with a 40 item statements.